Strategi Pengelolaan Kelas dalam Pembelajaran Pendidikan Agama Islam Peningkatkan Prestasi Belajar Siswa (Studi Kasus MTS Gaza Al-Islami Tanah Sareal Kota Bogor) - Juniarsih, Mahdalena; Nugraha, Aa; Srihartini, Yusi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic Religious Education (PAI) teachers at the MTS Gaza Al-Islami Islamic Boarding School, Tanah Sareal, Bogor City, the background to this problem is that PAI teachers face many obstacles in managing classes. MTS Based at the Gaza Al-Islami Tanah Sareal Islamic Boarding School, Bogor City, has tried to implement classroom management strategies well and optimally. This is proven by several achievements in the academic and non-academic fields. The aim of this research is to describe classroom management strategies in improving the achievement of students at MTS Gaza Al-Islami Tanah Sareal, Bogor City, as well as describing the obstacles and solutions to overcome the obstacles faced. This research is field research. The findings in this research are classroom management strategies in Islamic Religious Education learning in improving student achievement at SMP Pondok Pesantren Gaza Al-Islami Tanah Sareal Bogor City which includes 4 (four) activities, namely structuring the learning environment, teaching methods for teachers (educators), administration classes, and managing behavior and providing motivation to students. The obstacles faced by teachers in implementing classroom management strategies consist of internal factors and external factors. Internal factors include motivational factors and students' psychological conditions. External factors include time constraints and media allocation. The inhibiting factors are the diverse characteristics of students, teachers/homeroom teachers who have different understandings of classroom management